Detection of lower limb deep vein thrombosis: Comparison between radionuclide venography and venous ultrasonography - Daris Theerakulpisut; Nantaporn Wongsurawat; Charoonsak Somboonporn (World Journal of Nuclear Medicine)
Deep vein thrombosis (DVT) is a serious medical condition that needs prompt diagnosis and treatment. The invasive gold standard contrast venography has largely been replaced by venous ultrasonography which is currently the imaging modality of choice for DVT diagnosis. Radionuclide venography (RNV) is an alternative test for DVT, but a few studies have directly compared RNV with venous ultrasonography. This study aims to determine the agreement between RNV and venous ultrasonography for diagnosis of DVT and to determine the predictive value of different RNV findings for the prediction of DVT as detected by venous ultrasonography. Imaging results from patients who underwent both RNV and venous ultrasonography for suspected DVT no more than 1 week apart were reviewed. Results from both modalities were compared to determine inter-modality agreement. A total of 121 venous segments from 102 lower limbs of 75 patients could be compared. The prevalence of DVT as detected by venous ultrasonography was 39%. RNV and venous ultrasonography had moderate agreement (73.6% agreement, κ =0.48, P < 0.0001). The absence of radiotracer activity from a deep venous segment had a positive predictive value (PPV) of 100% for DVT. Other findings such as isolated great saphenous vein activity had a lower PPV. The negative predictive value of RNV is 97.5% with only one patient out of forty with normal RNV found to have DVT by venous ultrasonography, which suggests that DVT can virtually be excluded in patients with normal RNV.